2017
DOI: 10.1111/1365-2435.12953
|View full text |Cite
|
Sign up to set email alerts
|

Photoperiodic cues regulate phenological carry‐over effects in an herbivorous insect

Abstract: Abstract1. To maximise their fitness, organisms need to synchronise their phenology with the seasonal variation in environmental conditions. Most phenological traits are affected by environmental abiotic cues such as photoperiod, temperature and rainfall. When individuals with complex life cycles fail to match one of the stages with the favourable environment, the negative conditions experienced may lead to carry-over effects and, thus, influence fitness in subsequent stages.2. In the winter moth, an herbivoro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 43 publications
0
24
0
Order By: Relevance
“…, Salis et al. ). A previous study has shown that both green and white light at night advances caterpillar emergence from the pupa stage (van Geffen et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…, Salis et al. ). A previous study has shown that both green and white light at night advances caterpillar emergence from the pupa stage (van Geffen et al.…”
Section: Discussionmentioning
confidence: 99%
“…The lack of fitness effects might be expected if the insects that Great Tits rely on to feed their young, caterpillars, also shift in response to light pollution. In fact, the development of Lepidoptera eggs and larvae is also sensitive to both temperature and photoperiod, although the relative importance of each depends on the species examined (Cox 1979, Fantinou et al 1996, Nabeta et al 2005, Tauber et al 2015, Salis et al 2018. A previous study has shown that both green and white light at night advances caterpillar emergence from the pupa stage (van Geffen et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…spring or wet season) is likely to have major impacts on fitness and be under strong selection (e.g. Salis, Hoorn, Beersma, Hut, & Visser, 2018).…”
Section: A More G Ener Al Hyp Othe S Is For the E Voluti On Of Dr Pmentioning
confidence: 99%
“…In contrast to temperature, photoperiod can be defined as a highly reliable environmental cue due to the constant variations in photoperiod across days and seasons for a given latitude and/or altitude (Bradshaw & Holzapfel, 2007;Jackson, 2009;Salis, van den Hoorn, Beersma, Hut, & Visser, 2018). The day length that triggers the incidence of seasonal activities (critical photoperiod) is linked to the length of the growing season and the timing of the onset of a specific season.…”
Section: Introductionmentioning
confidence: 99%